2016
DOI: 10.1128/jvi.03198-15
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Assembly and Budding of Lujo Virus

Abstract: cThe recently identified arenavirus Lujo virus (LUJV) causes fatal hemorrhagic fever in humans. We analyzed its mechanism of viral release driven by matrix protein Z and the cell surface glycoprotein precursor GPC. The L domains in Z are required for efficient virus-like particle release, but Tsg101, ALIX/AIP1, and Vps4A/B are unnecessary for budding. LUJV GPC is cleaved by site 1 protease (S1P) at the RKLM motif, and treatment with the S1P inhibitor PF-429242 reduced LUJV production.T he family Arenaviridae i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Knockdown of the ESCRT-I protein TSG101 results in decreased VLP production for LCMV and LASV (17,42). Perturbation of the ESCRT accessory protein VPS4 reduces VLP production for Tacaribe virus and LASV but not Lujo virus (41,47,94). Recently, our laboratory has shown that LCMV utilizes the ESCRT complex specifically for defective interfering particle production but not the release of infectious virus (44).…”
Section: Discussionmentioning
confidence: 99%
“…Knockdown of the ESCRT-I protein TSG101 results in decreased VLP production for LCMV and LASV (17,42). Perturbation of the ESCRT accessory protein VPS4 reduces VLP production for Tacaribe virus and LASV but not Lujo virus (41,47,94). Recently, our laboratory has shown that LCMV utilizes the ESCRT complex specifically for defective interfering particle production but not the release of infectious virus (44).…”
Section: Discussionmentioning
confidence: 99%
“…The S segment of the viral genome encodes the glycoprotein (GP) precursor and the nucleoprotein, and the L segment encodes the matrix protein (Z) and the RNA-dependent RNA polymerase (L) ( 2 , 7 ). GP is synthesized as a single polypeptide chain and cleaved posttranslationally into GP1 and GP2 by a cellular proprotein convertase, subtilisin kexin isozyme 1/site 1 protease ( 8 , 9 ). GP1 is located on the top of the viral surface GP spike and mediates the attachment of virions to the target cell.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Z protein plays a crucial role in virion assembly and release (2,13,17). Although the importance of viral late domain motifs in Z protein and the interaction of Z protein with the cellular endosomal sorting complexes required for transport (ESCRT) for virion formation and budding have been well studied (2,13,(17)(18)(19)(20)(21)(22), the transport of Z proteins is been yet fully understood. In the present study, we performed live-cell imaging analyses of Z protein transport in LCMV-infected cells and characterised the movement both over short time period (within 3 min, not certified by peer review) is the author/funder.…”
Section: Introductionmentioning
confidence: 99%